2023
DOI: 10.1101/2023.08.28.555062
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discovery of 2-amide-3-methylester thiophenes that target SARS-CoV-2 Mac1 and repress coronavirus replication, validating Mac1 as an anti-viral target

Sarah Wazir,
Tomi A. O. Parviainen,
Jessica J. Pfannenstiel
et al.

Abstract: The COVID-19 pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus has made it clear that further development of antiviral therapies will be needed to combat additional SARS-CoV-2 variants or novel CoVs. Here, we describe small molecule inhibitors for SARS-CoV-2 Mac1, which counters ADP-ribosylation mediated innate immune responses. The compounds inhibiting Mac1 were discovered through high-throughput screening (HTS) using a protein FRET-based competition assay and the best hit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Molecular docking of compound 15c suggested that the pyrrolopyrimidine core mimics the adenine ring of ADPr while the carboxylic acid is placed at the oxyanion subsite. In a very recent manuscript, compound 27 ( Figure 1 ) 16 was identified as a moderate SARS-CoV-2 Mac1 inhibitor that is effective in cells. The co-crystal structure of this compound with SARS-CoV-2 Mac1 indicates that its carboxylic acid can also interact with the oxyanion subsite.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular docking of compound 15c suggested that the pyrrolopyrimidine core mimics the adenine ring of ADPr while the carboxylic acid is placed at the oxyanion subsite. In a very recent manuscript, compound 27 ( Figure 1 ) 16 was identified as a moderate SARS-CoV-2 Mac1 inhibitor that is effective in cells. The co-crystal structure of this compound with SARS-CoV-2 Mac1 indicates that its carboxylic acid can also interact with the oxyanion subsite.…”
Section: Introductionmentioning
confidence: 99%